The Evaluation of Nosocomial Candidemia in Pediatric Intensive Care: A Single-center Study - Hatice Feray Arı; Murat Arı (Galenos Yayinevi, 2023)
Objective: Patients in pediatric intensive care units are more likely to develop serious nosocomial infections due to comorbidities, longer and more invasive procedural treatments, and the development of immunosuppression. We described Candida infections, management, morbidity and mortality in critically ill pediatric patients. Materials and Methods: A retrospective single-center study includes patients aged 1 month-18 years treated against candidemia from January to December 2021. This included those who had blood cultures of Candida species growth. We excluded patients with infection Candida in endotracheal aspiration and/or urinary specimens, etc. The demographic characteristics, medical histories, comorbidities, length of stay, need for mechanical ventilation supports, laboratories, relationship use of catheters and total parenteral nutrition, treatment periods, antifungal response/resistance, duration of treatment and adverse effects, morbidities/mortalities. Results: In this study, the total mortality rate was 40.7%, and the mortality rate due to candidemia was detected at 44.4%, but the correlation between candidemia and mortality was not significant (p=0.975). However, 18.5% of them are caused by nosocomial. The mortality risk did not change for subtypes (p=0.975). No significant correlation was found when mortality (p=0.07) and central venous catheter infection (p=0.563) were compared using total parenteral nutrition. Conclusion: In our study, in which 27 patients were followed up for nosocomial candidemia, the rate of candidemia was found to be higher in patients with comorbidity, long-term mechanical ventilation support, central venous catheter use, long hospital stay, parenteral nutritional support, and high Pediatric Risk of Mortality III score. C. parapsilosis was detected most frequently in our Candida subtype unit with a rate of 59.3%. The fluconazole 8 (29.6%), amphotericin B 18 (66.7%) and voriconazole 1 (3.7%) patients were initiated. At this treatment time, only 4 (14.8%) patients developed organ failure. In our study, we detected a total mortality rate of 40.7%. However, 18.5% of them were caused by nosocomial candidemia. Considering all these reasons, we believe that our risk factors, diagnosis, treatment, follow-up, and management process will contribute to the literature.